Organizational factors, perceived acceptance and behavioral intention as dimensions of knowledge management readiness - Mohamed Razi, Mohamed Jalaldeen; Nor Shahriza, Abdul Karim; Norshidah, Mohamed (2014)
The concept of organizational readiness for knowledge management (KM) has been studied extensively from different perspectives in the recent past. KM supportive organizational factors such as KM oriented organizational culture, organizational structure and information technology infrastructures, and factors of individual acceptances are believed to be the predictors of KM readiness. However, the nature of those factors arguably suggests that they may not merely the predictors; rather they can be the dimensions of KM readiness. This work tries to verify this hypothesis. For this purpose, a questionnaire was formulated based on established measures, and administered using survey research methodology approach on 313 executives working in the selected organizations in the Sri Lankan telecommunication industry. The first order measurement model using AMOS version 16 was used to validate the measurement employed. Subsequently, a second order analysis was performed to test the hypothesis. Findings shows that all model fit indices are good and all the structural coefficients are significant, thus, the model fit to the data. Therefore, the current work proposes that the KM oriented organizational factors, individual acceptance and behavioral intentions should be considered as the dimensions of KM readiness.